Health аs а Sphere оf Formation оf Human Capital: the Problems of the Activation - O. Grishnova; O. Brintseva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2019)
The dynamics of processes of human capital formation in the sphere of healthcare is investigated. The trends, processes and asymmetries in this area that accompany the gradual market transformation of the national health system are often characterized, and often provoke the formation of unproductive forms of human capital and the processes of fiktivization. The system of indicators for estimating nominal and real human capital is proposed. The dynamics of nominal human capital is estimated by the following indicators: the growth of the rate of the number of doctors of all specialties per 10 thousand population; the growth rate of the number of average medical personnel per 10 thousand population; the growth rate of the planned capacity of outpatient clinics for 10 thousand people. To assess the dynamics of nominal human capital: growth rate of the average life expectancy at birth (without gender differentiation); the growth rate of the disease per 100 thousand population (all diseases). According to our methodology, the growth of the index of real human capital shows progress in the medical sphere. The growth of the nominal human capital index shows an increase in spending on this area, and it does not always indicate progress, although its substantial reduction is alarming and requires a more detailed analysis. If real human capital grows faster than nominal, then healthcare activities are effective, and if on the contrary – in this area the processes of fictivization takes place. Recommendations for reducing the fiktivization processes in the sphere of healthcare are proposed, which include: development and implementation of a system for monitoring the quality of medical services on the basic data of the eHealth system; the further introduction of digital technologies into the national health system and, on this basis, – increasing the availability of analytical information for both medical professionals and researchers, and for the public, the dissemination of medical literacy and healthy lifestyles.